Ethnoscience-Based Climate Change Adaptation: Survival Strategies for Agricultural Communities in Panimbang Regency - Okta, Setyo Luthfi; Saefullah, Rifki (International Journal of Ethno-Sciences and Education Research, 2025)
Climate change is a global challenge affecting the agricultural sector, particularly in agrarian areas such as Panimbang Regency, Banten. This study aims to identify and analyze climate change adaptation strategies based on local knowledge or ethnoscience implemented by farming communities. Using a descriptive qualitative approach with an ethnographic orientation, data were collected through in-depth interviews, participatory observation, focus group discussions, and visual documentation. The results revealed five key adaptation strategies: observing natural signs, adjusting the planting calendar based on phenology, water management with traditional irrigation systems, crop diversification, and cultural and ritual practices. These strategies have been shown to increase community resilience to climate variability by reducing the risk of crop failure and maintaining ecological balance. The high adoption rate of crop diversification and observing natural signs emphasizes the relevance of local knowledge amidst the dominance of technocratic approaches. This study emphasizes the importance of recognizing, preserving, and integrating ethnoscience knowledge into climate adaptation policies to be more inclusive and contextual. Thus, local wisdom serves not only as a cultural heritage but also as a dynamic framework that supports food security, environmental sustainability, and the well-being of farming communities in the era of climate change.